The Development of Late Adolescents in Physical, Intellectual, Emotional, Social, Moral, and Religious Aspects and Its Implications for Islamic Education - Qomariyah, Nurul; Romadhon, Muhammad Qomari; Harto, Kasinyo; Suryana, Ermis (Jurnal Pendidikan Islam, 2025)
Late adolescence is an important phase in the formation of students’ self-identity and character, so that Islamic religious education has a strategic role in directing this development as a whole. This study aims to examine the development of late adolescents in physical, intellectual, emotional, social, moral, and religious aspects and their implications for Islamic education at Madrasah Aliyah Nurul Iman Banyuasin. This research uses a qualitative approach with a field study method. Data were collected through in-depth interviews, observations, and documentation of students, PAI teachers, and the head of madrasah. The results showed that although there is progress in physical and intellectual aspects, the main challenges are still found in the emotional, moral aspects, and the practice of religious teachings in daily life. Therefore, Islamic education needs to be developed with a contextual, reflective, and applicable approach through adaptive learning methods and consistent exemplary behavior. Thus, students are expected to be able to internalize Islamic values more deeply and apply them in various aspects of life.